Multiplicative dependence of cubic algebraic numbers - Drungilas, Paulius; Klimavičius, Linas (Lietuvos matematikos rinkinys, 2017)
We provide an infinite family of cubic algebraic integers α such that the set {α + x | x ∈ Z} is multiplicatively dependent.
Keywords: algebraic numbers; multiplicative dependence.